Impact of computer use and academic achievement in the first year of secondary school from the point of view of Jerusalem teachers - Alessa, Inas Abbad; Nemer, Heyam (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the impact of computer use on academic achievement in the first year of secondary school from the point of view of Jerusalem teachers. The tool was validated and distributed to a sample of (98) teachers who were chosen randomly. The study found the following: •There is a clear impact of the computer on the academic achievement of first year secondary school students from the teachers’ point of view, where the arithmetic mean of teachers’ attitudes was (3.94), which is a high average. •There are no statistically significant differences between teachers’ attitudes in the impact of computer use on academic achievement in the first year of secondary school due to the gender variable. There are no statistically significant differences between teachers’ attitudes in the impact of computer use on academic achievement in the first year of secondary school due to the variable years of experience. There are statistically significant differences between teachers’ attitudes in the impact of computer use on academic achievement in the first year of secondary school due to the educational qualification variable. The study recommended the following: Qualifying teachers and raising their educational competencies in the use of computers and the recruitment and preparation of computer programs through training courses and specialized workshops. Follow up on developments and developments in the field of using computers in the educational process and adopt successful experiences in employing computers in the educational process. Investing in teachers’ positive attitudes towards the use of computers to adopt these trends and employ them in the learning process. Carrying out other studies similar to the current study at different educational stages, while specifying a subject in itself. In favor of the diploma, and in light of the results, the researchers presented a number of recommendations and suggestions.